Noninvasive Brain Stimulation and Noninvasive Peripheral Stimulation for Neglect Syndrome Following Acquired Brain Injury. Issue 3 (14th November 2019) - Lucente, Giuseppe; Valls‐Sole, Josep; Murillo, Narda; Rothwell, John; Coll, Jaume; Davalos, Antoni; Kumru, Hatice
Abstract : Objective: Hemispatial neglect is a frequent condition usually following nondominant hemispheric brain injury. It strongly affects rehabilitation strategies and everyday life activities. It is associated with behavioral and cognitive disability with a strong impact on patient's life. Methods: We reviewed the published literature on the use of noninvasive brain stimulation, including repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS), and of noninvasive peripheral muscle stimulation, as therapeutic strategies for rehabilitation of neglect after acquired brain injury, such as in stroke or in traumatic injuries. The studies were grouped as controlled or uncontrolled studies in each stimulation techniques. Results: Thirty‐four studies were identified and 16 on rTMS, 10 on tDCS, and 8 on vibration. All studies were conducted in adult patients who suffered a stroke, except for one that was conducted in a patient suffering traumatic acquired brain injury and another that was conducted in a patient with brain tumor. In spite of significant variability in treatment protocols, patients' features and assessment of neglect, improvement was reported in almost all studies with no side‐effects. Conclusions: Noninvasive brain stimulation and neuromuscular vibration are promising therapeutic neuromodulatory approaches for neglect. Further randomized‐controlled studies are needed to corroborate their effectiveness as separate and combined techniques.